2013
DOI: 10.2139/ssrn.2385991
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Market Power in an Exhaustible Resource Industry. The Case of Rare Earth Elements

Abstract: Die Dis cus si on Pape rs die nen einer mög lichst schnel len Ver brei tung von neue ren For schungs arbei ten des ZEW. Die Bei trä ge lie gen in allei ni ger Ver ant wor tung der Auto ren und stel len nicht not wen di ger wei se die Mei nung des ZEW dar.Dis cus si on Papers are inten ded to make results of ZEW research prompt ly avai la ble to other eco no mists in order to encou ra ge dis cus si on and sug gesti ons for revi si ons. The aut hors are sole ly respon si ble for the con tents which do not neces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Optimistic scenarios as in Pothen (2013Pothen ( , 2014 appear less likely. If China is able to restrict exports using the licensing system, it can retain its influence on rare earth markets.…”
Section: New Non-chinese Suppliersmentioning
confidence: 96%
See 1 more Smart Citation
“…Optimistic scenarios as in Pothen (2013Pothen ( , 2014 appear less likely. If China is able to restrict exports using the licensing system, it can retain its influence on rare earth markets.…”
Section: New Non-chinese Suppliersmentioning
confidence: 96%
“…The entry of non-Chinese suppliers could deteriorate China's market power (Pothen, 2013(Pothen, , 2014.…”
Section: Supplymentioning
confidence: 99%
“…With the beginning of the WTO trial, three rather than two quota announcements were issued each year, which were favourable for global REEs users and non-Chinese REEs suppliers (Mueller et al 2014). Pothen (2013) estimates the impact of REEs export restrictions on the Chinese market power and corresponding welfare effects by applying a dynamic partial equilibrium model. The business-as-usual simulation, which assumes export restrictions at the level of 2013, showed that China would be able to utilize its market power to affect prices until 2019.…”
Section: Impact Of Regulatory Adjustment On Pricing and Market Powermentioning
confidence: 99%
“…China's welfare gains are 1.4 billion US $ in this scenario, while the rest of the world would incur welfare losses of 1.96 US$. The end of Chinese market power in this scenario would be the market entry of REEs suppliers outside of the PRC (Pothen 2013). The development of new mines, the re-opening of old mines like the Mountain Pass mine, which can be economically exploited again due to high REEs prices, research and development efforts to find substitutes and recycling possibilities and the trade diversification of REEs suppliers were all triggered by the Chinese adjustment of the trade regime (Seaman 2012).…”
Section: Impact Of Regulatory Adjustment On Pricing and Market Powermentioning
confidence: 99%
“…In this regard, some scholars have classified both Scandium and yttrium into the heavy element category. [11][12][13] On the other hand, some others have highlighted that the third category RE can be classified as medium rare earth (MREEs) which refers to the elements of Sm, Eu, and Gd. [14][15][16] It is noteworthy that there are six different ores mineral from industry productions which include bastnasite [(Ce,La)(CO 3 )F], monazite [(Ce,La)PO 4 )], xenotime (YPO 4 ), loparite[(Ce,Na,Ca)(Ti,Nb)O 3 ], apatite [(Ca,REE,Sr,Na,K) 3 Ca 2 (PO 4 ) 3 (F,OH)], and ionadsorption clays.…”
Section: Introductionmentioning
confidence: 99%